THE EFFECT OF LEARNING STYLES AND GADGET USAGE ON STUDENT LEARNING OUTCOMES IN DIGITAL SIMULATION SUBJECTS: A QUANTITATIVE STUDY AT VOCATIONAL HIGH SCHOOL - Tutut Wi Veren; Fahrur Rozi (STKIP PGRI TULUNGAGUNG, 2025)
This study investigates the effect of learning styles and gadget usage on student learning outcomes in the Digital Simulation (SIMDIG) subject at SMK Negeri 2 Tulungagung, Indonesia. Despite the widespread integration of digital devices in secondary education, empirical evidence on how unregulated gadget use and individual learning styles jointly affect academic performance in vocational settings remains limited. Employing a quantitative non-experimental correlational design, this study collected data from 76 Grade X students selected through purposive sampling from a population of 505. Data were gathered using a closed Likert-scale questionnaire and documentation of KD 3.9 scores. Multiple linear regression analysis was conducted following prerequisite tests for normality (Kolmogorov–Smirnov), linearity, and multicollinearity. Results revealed that learning style does not significantly predict learning outcomes (t = 0.842, p = 0.403 0.05), while gadget usage demonstrates a significant negative effect on learning outcomes (t = 2.274, p = 0.026 0.05). Simultaneously, both variables do not produce a combined significant effect (F = 2.736, p = 0.071 0.05). These findings suggest that while individual learning styles may require more targeted instructional mediation to manifest effects on academic performance, gadget misuse during instructional time represents a salient and actionable predictor of reduced learning outcomes. Implications for teachers, school administrators, and educational technology policymakers are discussed.